Mini-Review: Gut-Microbiota and the Sex-Bias in Autoimmunity – Lessons Learnt From Animal Models - Rosser, Elizabeth C.; de Gruijter, Nina M.; Matei, Diana E. (Frontiers in Medicine, 2022)
It is well appreciated that there is a female preponderance in the development of most autoimmune diseases. Thought to be due to a complex interplay between sex chromosome complement and sex-hormones, however, the exact mechanisms reasons underlying the sex-bias remain unknown. In recent years, there has been a focus on understanding the central pathogenic role of the bacteria that live in the gut, or the gut-microbiota, in the development of autoimmunity. In this review, we discuss evidence from animal models demonstrating that the gut-microbiota is sexually dimorphic, that there is a bidirectional relationship between the production of sex-hormones and the gut-microbiota, and that this sexual dimorphism within the gut-microbiota may influence the sex-bias observed in autoimmune disease development. Collectively, these data underline the importance of considering sex as a variable when investigating biological pathways that contribute to autoimmune disease risk.